New physics in spin entanglement - Mateusz Duch; Alessandro Strumia; Arsenii Titov (European Physical Journal C: Particles and Fields)
Abstract We propose a theory that preserves spin-summed scattering and decay rates at tree level while affecting particle spins. This is achieved by breaking the Lorentz group in a non-local way that tries avoiding stringent constraints, for example leaving unbroken the maximal sub-group SIM(2). As a phenomenological application, this new physics can alter the spins of top-antitop pairs (and consequently their entanglement) produced in pp collisions without impacting their rates. Some observables affected by loops involving top quarks with modified entanglement receive corrections.